1994
DOI: 10.1093/oxfordjournals.eurheartj.a060391
|View full text |Cite
|
Sign up to set email alerts
|

Volume loading in predominant right ventricular infarction: bedside haemodynamics using rapid response thermistors

Abstract: Intravenous fluid loading is commonly used for the treatment of low cardiac output (CO) syndrome complicating severe right ventricular infarction (RVMI). We prospectively evaluated the effectiveness of this method in 11 consecutive patients (age 66 +/- 14 years) with severe RVMI, using a newer thermodilution method with rapid response thermistors. Volume loading was performed until pulmonary wedge pressure (PWP) reached 18 to 24 mmHg. Right atrial pressure (RAP), pressures of the right ventricle (RV) and pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…There is a wide variation in its response, but no clear linear association was noted between PWP and cardiac index with a higher right-sided filling pressure target. [47][48][49][50][51] associated with a higher recovery rate of RV function by echocardiography and better 30-day mortality than incomplete revascularization in patients with RV infarction. Further, in cases of complication with ventricular arrhythmia, reperfusion results in a better prognosis.…”
Section: Early Revascularizationmentioning
confidence: 99%
“…There is a wide variation in its response, but no clear linear association was noted between PWP and cardiac index with a higher right-sided filling pressure target. [47][48][49][50][51] associated with a higher recovery rate of RV function by echocardiography and better 30-day mortality than incomplete revascularization in patients with RV infarction. Further, in cases of complication with ventricular arrhythmia, reperfusion results in a better prognosis.…”
Section: Early Revascularizationmentioning
confidence: 99%
“…In these circumstances, however, determining if 'responsiveness' to fluid therapy can translate into the actual need for fluid therapy remains largely unknown. In right ventricular shock, small studies have found that fluid therapy alone can inconsistently impact cardiac output [103][104][105]. Excessive fluid therapy may dilate the right ventricle, worsen cardiac output, induce right ventricular endocardial ischemia, precipitate ischemic hepatitis and lead to death.…”
Section: Fluid Therapy In Cardiogenic Shockmentioning
confidence: 99%
“…found that right-ventricular end-diastolic volume measured by pulmonary artery catheter was not a reliable predictor of fluid responsiveness in patients under MV, and that Ppao and RAP were superior to rightventricular end-diastolic volume. The discrepancy between the results of these studies may partly reflect the measurement errors of cardiac output due to the cyclic change induced by positive pressure ventilation [59, 60,61,62], the inaccuracy of cardiac output measurement obtained by pulmonary artery catheter when the flux is low [63], and the influence of tricuspid regurgitation on the measurement of cardiac output [64]. Moreover, as rightventricular end-diastolic volume is calculated (stroke volume divided by right ejection fraction), cardiac output becomes a shared variable in the calculation of both stroke volume and right-ventricular end-diastolic volume, and a mathematical coupling may have contributed to the close correlation observed between these two variables.…”
Section: Ppao Used To Predict Fluid Responsivenessmentioning
confidence: 99%